(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Il Regolamento UE 2016/679 e i dati di natura religiosa: un nuovo percorso normativo da analizzare - 2. Dalla legge n. 675 del 1996 al d.lgs. n. 196 del 2003: l’affermarsi delle “autorizzazioni generali” per il trattamento dei dati sensibili da parte delle confessioni religiose - 3. Le novità introdotte dal Regolamento europeo n. 679 del 2016 per il trattamento dei dati di natura religiosa e il mancato riferimento alle “autorizzazioni generali” - 4. Il d.lgs. n. 101 del 2018 e l’adeguamento italiano alla normativa comunitaria del 2016: il recupero delle “autorizzazioni generali” - 5. Il ruolo del Garante e la conferma parziale della legittimità dell’autorizzazione generale n. 3 - 6. Un nuovo ruolo per i responsabili del trattamento dei dati di natura religiosa: privacy by design, compliance normativa e tutela dell’autonomia delle confessioni religiose. General Authorizations to process of sensitive data by churches. Considerations on recent reforms in theme of privacy ABSTRACT: The Regulation (EU) 2016/679 – so-called GDPR - has resulted in a significant reform of the Italian system for the protection of personal data and crystallized in Legislative Decree no. 196 of 30 June 2003. The GDPR, which focuses on principle of accountability and the concepts of privacy by design and privacy by default, has rethought, in particular, the category of data in which those of a religious nature were inserted basing their discipline on a general prohibition of treatment and provided that churches, associations or religious communities can dictate and apply their own internal legislation in this field, provided that it complies with the community provisions of the regulation. Before entry into force of the GDPR, the processing of religious data was mainly linked to the provision by the Guarantor Authority for the protection of personal data of a General Authorization - No. 3 - which allowed religious confessions to process the data of their members. This system has been questioned in part by the GDPR and then re-read by Legislative Decree no. 101/2018, which confirmed the value of the General Authorization n.3 in the framework of a peculiar system of guarantees.